Programma: 9 april Grunge funk party; 11 april Raymonde & Orchestre "El Hajoui"; 17 april Tania Libertad; 18 april Lucky Dube
Programma: 9 april Grunge funk party; 11 april Raymonde & Orchestre "El Hajoui"; 17 april Tania Libertad; 18 april Lucky Dube.